Changing dynamics of caregiving: a meta-ethnography study of informal caregivers' experiences with older immigrant family members in Europe - Sunita Shrestha; Sanjana Arora; Alistair Hunter; Jonas Debesay (BMC, 2023)
Abstract Background The population of Europe is ageing and becoming more ethnically diverse due to migration. Finding suitable long-term caring arrangements for older immigrants in Europe has been one of healthcare policymakers' concerns in the last decade. However, relatively few older people with an immigrant background live in long-term care facilities, and many prefer to be cared for by their family members. Little is known about immigrant family caregivers' experiences of caring for older family members and the support they need while providing care. This study aims to synthesize the qualitative literature exploring the experiences of individuals caring for older family members with immigrant backgrounds from Africa, Asia and South America living in Europe. Methods We searched the electronic databases Medline Ovid, Embase Ovid, PsycInfo Ovid, SocIndex EBSCOhost, CINAHL EBSCOhost, Scopus, Social Care Online, ASSIA ProQuest, and Google Scholar for original, peer reviewed research articles, published in English from 2011 to 2022. The seven-step interpretive methodology in meta-ethnography developed by Noblit and Hare (1988) was followed for qualitative synthesis. Results After assessing 4155 studies for eligibility criteria, 11 peer-reviewed articles were included in this review. The qualitative synthesis of these included articles resulted in four main themes: strong care norms for parents, the moral dilemma of continuing care, uneven care sharing, and the use of formal care services. Conclusions Caregiving dynamics are changing, both in terms of motivations and approaches to caregiving. Furthermore, there are gender disparities in the distribution of caregiving duties, particularly with women carrying the more significant burden of care. The care burden is further exacerbated by the lack of culturally sensitive formal services complementing the care needs of the ageing immigrants and their family caregivers. Therefore, those searching for alternatives to informal care should be met with appropriate health and care services in terms of language, culture, religion, and lifestyle, delivered in a non-judgmental way.